Assessing the validity and applicability of the French 3‐year prognostic score in the UK cystic fibrosis population ‐ a national cohort study. (24th January 2021) - Frost, Freddy; Nazareth, Dilip; Shaw, Matthew; Al‐Aloul, Mohamed
Summary: Models that predict outcomes, aid prognostication and inform the assessment of urgency for lung transplantation (LT) in CF are in demand. A prognostic score derived from the French adult CF registry to predict death or LT over 3‐year follow‐up was described in 2017 and validated using Canadian CF registry data. We assessed its performance in the UK CF population. The French prognostic score was applied to untransplanted adults with CF. The index year (2014) and outcomes (Death or LT) were evaluated to 2017. Receiver operator characteristics plots and area under curve (AUC) was computed. 4407 adults with CF met the inclusion criteria. After 3 years, 7.1% ( P  < 0.001) were dead or had received LT compared to the French (12.8%) and Canadian (9.4%) cohorts. The French score deemed 592 (26.2%) 'High‐risk' ‐ death/LT occurred in 189/592 (30.2%), less than previously reported in France and Canada ( P  < 0.0001). The discriminatory power of the French score was lower (AUC 0.830) than reported. Recalibration yielded only marginal improvement in model performance (AUC 0.833). The French prognostic score does not perform as well in the UK as reported elsewhere. Bespoke UK scores are needed to aid prognostication and inform LT decision‐making.